A New Method for the Sputum Cytology Test Without Direct Contact to Specimens During COVID-19 Pandemic - Cui, Junqi; Wang, Xia; Rao, Yamin; Ji, Tianhai; Li, Long (Frontiers in Medicine, 2022)
Background：The coronavirus disease 2019 (COVID-19) pandemic continues to spread across the world. Specimens of blood, body fluids and excreta received in the department of pathology undoubtedly increased the risk of infection, especially in some hospitals that are short of professional protection capability. Here we provided a new simple way for sputum cytology test during COVID-19 pandemic. Methods：Sputum samples from 30 patients with lung cancer were collected and divided into two groups, including control and experimental group. Samples of control group were processed in the biological safety cabinet, while the experimental group was put into the sealed specimen bag directly and pretreated with 75% medical alcohol. Then the cell morphology and tumor cell identification were analyzed by cell smears and liquid-based cells staining. The expression of cell antigens was determined by immunohistochemical staining. Result: Our result showed that both sputum samples in two groups exhibited complete cell structure and clear morphology according to the cell smear and liquid-based cells staining. In addition, immunohistochemical result showed that cell antigens including CK, LCA and TTF1were specifically expressed in cell membrane, cytoplasm and nucleus, respectively. The tumor cells were distributed diffusely and cell antigens were located accurately after pretreatment with 75% medical alcohol, which were consistent with that of the control group. Conclusion：Using 75% medical alcohol to pretreat sputum specimen has no obvious impact on cell morphology and antigens expression. Our study provided a new method for the sputum cytology test with no direct contact so that to protect medical staff against virus during COVID-19 outbreak.